2022
DOI: 10.3390/en15207683
|View full text |Cite
|
Sign up to set email alerts
|

Promising and Potential Applications of Phase Change Materials in the Cold Chain: A Systematic Review

Abstract: Appropriate measures have been taken to reduce energy requirements for cold chain applications. Thermal energy storage is an accepted method to reduce the need for electrical energy after harvesting fresh horticultural produce. The use of phase change materials (PCM) in postharvest storage, outside of a temperature-controlled environment, extends shelf life and keeps food at the ideal temperature. This review focuses on the various trials using PCM to improve cold chain effectiveness. It also discusses the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…The use of TES has already found application in many fields [16], and it has been shown that they can significantly increase the efficiency of energy systems, e.g., photovoltaic panels [17]. TES systems are also very promising in the cold chain industry [18]. Cold TES can either use latent heat mediums like phase change materials (PCM) or sensible heat mediums.…”
Section: Introductionmentioning
confidence: 99%
“…The use of TES has already found application in many fields [16], and it has been shown that they can significantly increase the efficiency of energy systems, e.g., photovoltaic panels [17]. TES systems are also very promising in the cold chain industry [18]. Cold TES can either use latent heat mediums like phase change materials (PCM) or sensible heat mediums.…”
Section: Introductionmentioning
confidence: 99%
“…This is where phase change materials (PCMs) come into play. Thermochemical storage, although having the highest energy storage capacity, grapples with long-term stability issues in controlled environments and has a complex and costly development process [15].…”
Section: Introductionmentioning
confidence: 99%
“…While this type of PCM has its applications, the solid-liquid class is most frequently employed due to its significantly higher latent heat of fusion. This facilitates greater energy storage and release during the phase transition process [15]. Prior studies indicate that temperature fluctuations during food transportation [8] and storage [12][13][14] can be detrimental to food quality and shelf life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation